2004
DOI: 10.1074/jbc.m311890200
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Structures of the Leucine-binding Protein Illustrate Conformational Changes and the Basis of Ligand Specificity

Abstract: The periplasmic leucine-binding protein is the primary receptor for the leucine transport system in Escherichia coli. We report here the structure of an open ligand-free form solved by molecular replacement and refined at 1.5-Å resolution. In addition, two closed ligand-bound structures of the same protein are presented, a phenylalanine-bound form at 1.8 Å and a leucine-bound structure at a nominal resolution of 2.4 Å. These structures show the basis of this protein's ligand specificity, as well as illustratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 38 publications
4
70
0
Order By: Relevance
“…Fig. 1 illustrates our first example, the L-leucine binding protein [Protein Data Bank (PDB) IDs 1usg and 1usi], which experiences large conformational changes upon binding to L-leucine (30). …”
Section: Resultsmentioning
confidence: 99%
“…Fig. 1 illustrates our first example, the L-leucine binding protein [Protein Data Bank (PDB) IDs 1usg and 1usi], which experiences large conformational changes upon binding to L-leucine (30). …”
Section: Resultsmentioning
confidence: 99%
“…Conformational changes of periplasmic SBPs, such as ribose-binding protein, allose-binding protein, leucine/isoleucine/₩ valine-binding protein, and leucine-binding protein, were intensively studied by X-ray crystallography (22)(23)(24)(25). These SBPs adopt a similar fold made of two lobes, which are connected by one or more polypeptide chains, forming a hinge.…”
Section: Discussionmentioning
confidence: 99%
“…A conformational change to either a larger or a smaller size plays an important role in the ligandbinding mechanism. In fact, conformational changes of the side chains of a binding site (Najmanovich et al 2000;Zavodszky and Kuhn 2005), small movements and/or deformation of loops (Malkowski et al 1997;Karthikeyan et al 2003), large-scale domain motions (Kraft et al 2002;Magnusson et al 2004;Amemiya et al 2012), and quaternary movements of subunits (Xiong et al 2002;Benison et al 2008) have been observed during the binding of a ligand to proteins. The intrinsic thermal motion of proteins is considered responsible for the conformational changes upon ligand binding.…”
Section: Ligand-induced Conformational Changementioning
confidence: 99%